Learning Model under Passing Volleyball for Students Junior High School - Agus Riyandi; Samsudin Samsudin; Iman Sulaiman (Universitas PGRI Palembang, 2023)
The problem of this research is that volleyball learning is less effective and less fun and even makes students find it difficult to carry out low-level learning, it is caused by the lack of teacher creativity in teaching that is attractive to students but still effective in achieving the goals designed in each lesson. The purpose of this study was to produce a product of the Volleyball Bottom Passing Learning Model in Junior High Schools. The learning model is later expected to be able to help teachers during the physical education learning process, especially in volleyball material. This study uses the ADDIE method. The results of the study resulted in a product in the form of a Volleyball Bottom Passing Learning Model in Junior High School which had been validated and revised by 18 models. Data were collected through documentation, interviews, and observations. The analysis was done descriptively. The results of the study were in the form of a book on the Learning Model of Lower Passing Volleyball in Junior High Schools. The results of this study are the bottom passing volleyball in the control group of 49.60 while the average result of the volleyball under passing in the experimental group is 56.73. It can be concluded that the results of the experimental group's volleyball bottom passing were better than the control group with a difference of 7.17. From the table above, it is obtained that the t count is 8.098 > t table is 2.001 with a significance level of 5% and P-Value 0.000 <0.05. It can be concluded that there is a significant and effective influence on junior high school students.